Characteristics and geochemical significance of heteroatom compounds in terrestrial oils by negative-ion electrospray Fourier transform ion cyclotron resonance mass spectrometry. (September 2017) - Wan, Zhonghua; Li, Sumei; Pang, Xiongqi; Dong, Yuexia; Wang, Zhengjun; Chen, Xiangfei; Meng, Xiangbing; Shi, Quan
Highlights: Abundant heteroatom compounds in crude oils/source rocks were identified by FT-ICR MS. Kerogen type has an impact on NO compounds in oil/source rocks. Maturity has a clear control on carbon number and condensation of NO compounds. Abstract: Terrestrial oils and rock extracts from the Nanpu Sag (Huanghua Depression, Bohai Bay Basin, China) were characterized by negative-ion electrospray ionization (ESI) Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) and gas chromatography mass spectrometry (GC-MS). Molecular composition of neutral nitrogen and acidic oxygen compounds, mainly by N1, O1, and O2 species were investigated in the samples. Increases in relative abundance and molecular condensation degree of oxygen-containing compounds and a decrease in the carbon number range of N1 species were observed with the changes of kerogen from Type I to III for both the source rock extracts and the relevant oils, which indicates the influence of source input and discrimination potential. We also observed an apparent increase in the condensation degree and a decrease in the carbon number of the N1, O1 and N1 O1 species with increasing maturity. The carbon numbers and double bond equivalent (DBE) values of the N1 and N1 O1 species in the extracts showed a positive relationship (an approximately linear distribution) during thermal evolution. These results indicate that thermal maturity has a crucial influence on the composition. The relative abundance ratios of N1 and O1 species with specific DBE values and carbon number ranges, C16–20 /C21–50 -DBE12 -N1, C20–24 /C25–50 -DBE15 -N1, C11–15 /C16–27 -DBE4 -O1, DBE12 /DBE9 -N1, and DBE8–9 /DBE4 -O1 are proposed as thermal maturity indicators for the evaluation of mature and post-mature source materials. A strong primary migration fractionation effect on the heteroatom compounds was also observed, implying that these compounds can be used as migration auxiliary proxies.